Phytoplankton growth and succession driven by topography and hydrodynamics in seasonal ice-covered lakes - Ziyue Zhao; Yanfeng Wu; Y. Jun Xu; Yexiang Yu; Guangxin Zhang; Dehua Mao; Xuemei Liu; Changlei Dai (Ecological Informatics)
Understanding how underwater topography affects phytoplankton succession by influencing hydrodynamics is crucial for maintaining the ecological health of lakes. However, there is a lack of in-depth research that accurately depicts underwater topography and coupleing hydrodynamics to establish the reproduction and migration mechanisms of phytoplankton, especially in seasonal ice-covered lakes. A typical seasonally ice-covered lake, Lake Chagan, was selected, and 164 water column and plankton samples were collected in 2023. An integrated underwater topographic-hydrodynamic model was constructed based on topographic data from 597 exploration points and long-term hydrological and meteorological observational data. The dominant algal species and their three-dimensional distribution and succession processes during different periods were studied in detail. The effects of topographic factors (relief, surface curvature, water depth, slope gradient, roughness, and slope aspect) on the hydrodynamic field and phytoplankton distribution were discussed. The results showed that the phytoplankton species diversity was higher in the bottom water column during the non-ice-covered period (March to October). The dominant species of phytoplankton varied with seasons, with diatoms dominating in the ice-covered period and harmful phytoplankton such as cyanobacteria in the non-ice-covered period. The biomass and biomass density of cyanobacteria were also higher than those of other phytoplankton. Phytoplankton species diversity and richness indices in the surface water column had a significant combined effect on the entire lake ecosystem. Surface curvature and slope gradient were the main factors affecting flow velocity during the non-ice-covered period (p ≤ 0.05, r = −0.58 and − 0.62), directly affecting the spatial distribution of cyanobacterial biomass (p ≤ 0.05, r = 0.65; p ≤ 0.01, r = −0.71). Therefore, attention should be paid to the surface curvature and slope of the sediment when controlling cyanobacterial blooms via by sediment dredging. These studies explored the behavior of phytoplankton in response to their fluid environment from a combined biological and physical-dynamic perspective and provided an effective reference for the water environment management of seasonal ice-covered lakes with harmful algal blooms.